Diversity of Species and Morphometrics of Reptiles (Order Squamata) in The Utilization Block of The Kerandangan Tourism Area - Ramadhan, Nuzul Rizki; Syaputra, Maiser; Wahyuningsih, Endah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This study aims to identify and analyze the diversity of reptiles from the order Squamata in the Kerandangan Nature Tourism Park, West Lombok Regency, West Nusa Tenggara Province, Indonesia, which has various habitat types, namely garden, secondary forest, riparian, and ecotone, influencing the distribution and adaptation of reptile species. The results showed that 11 species of reptiles from the order Squamata were found, consisting of 7 species of snakes and 4 species of lizards. The diversity, richness, and evenness indices of species varied across each habitat type, with the highest diversity index found in the riparian habitat (H’ = 1.64) and the lowest in the ecotone habitat (H’ = 1.28). The dominance index revealed that Dendrelaphis pictus dominated the ecotone habitat, while Gekko gecko dominated the garden habitat. Morphometric analysis showed variations in body size between species, with the reticulated python (Malayopython reticulatus) having the largest total length (375 cm) and the snail snake (Pareas carinatus) having the smallest size (47 cm). These results illustrate the adaptation of reptile species to diverse ecological conditions in the Kerandangan Nature Tourism Park. This study is expected to contribute to understanding biodiversity and the importance of reptile habitat conservation in the nature tourism park. Kerandangan Nature Tourism Park, located in West Lombok Regency, has abundant biodiversity, with reptiles from the order Squamata being an important part of its ecosystem. This research is crucial to understanding the diversity, abundance, and distribution of reptiles in the Kerandangan Nature Tourism Park as part of conservation efforts that can provide valuable data and information for managing the area.